Employees’ empowerment and maturity levels of corporate environmental management in companies: a framework - Jabbour, Charbel José Chiappetta; Santos, Fernando Almada (Revista de Administração da UFSM, 2013)
This paper discusses a human resource management dimension that is rarely integrated with the theme of corporate environmental management: the employees’ empowerment .Indeed, human resources dimensions are considered non-technical factors that directly affect the integration of environmental performance in companies. Among these dimensions of human resources necessary for environmental management, we highlight the empowerment of employees. Thus, this research provides theoretical basis on environmental management in company and on employee empowerment and the integration of these themes. Finally, a framework for an effective corporate environmental management through empowerment is presented. We intend to contribute in this way for management researchers and organizational leaders, within a scope still scarce of theoretical articulations.